Jewish Nationality and Soviet Politics : The Jewish Sections of the CPSU, 1917-1930 - Gitelman, Zvi Y. (Book collections on Project MUSE., 1972)
In order to "Bolshevize" the Jewish population, the Soviets created within the Party a number of special Jewish Sections. Charged with the task of integrating the largely hostile or indifferent Jews into the new state the Sections' programs are, in effect, a case study of the modernization and secularization of an ethnic and religious minority. Zvi Gitelman's analysis of the Sections during the first decade of Soviet rule examines the nature of the challenge that modernization posed, the crises it created, and the responses it evoked.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.